EDUKASI AGRIKULTURALBERBASIS KEBUN MINI HIDROPONIK SEBAGAI UPAYA MEMBANGUN KEMANDIRIAN PANGAN PADA ANAK SEKOLAH DASAR DALAM PERSPEKTIF PENDIDIKAN ISLAM - Achmad Anwar Abidin; Muhammad Sulaiman; Nova Tri Prasetiyo; Sariyani Sariyani; Muhammad Farizal Amri; Imam Syafi'i; Sidik Puryanto; Ahmad Yani; Juli Firmansyah (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This community service program aims to increase environmental awareness and food independence in elementary school students through agricultural education based on hydroponic mini gardens with the integration of Islamic Education values. This study uses a Participatory Action Research (PAR) approach involving 33 grade V students of SDN 03 Tonjong, teachers, and the school community in four stages: planning, action, observation, and reflection. Activities include hydroponic training, construction of mini gardens, planting vegetables (kale and pakcoy), and integration with science subjects. The program successfully increases students' enthusiasm and understanding of sustainable agriculture. Students are actively involved in the process of planting to maintaining plants, and teachers integrate these activities into science learning as an ongoing practice. The PAR approach with hydroponic mini gardens is effective in building environmental awareness and food independence in elementary school children, while instilling Islamic values about ecological responsibility as a caliph on earth.